PENGARUH MOTIVASI KERJA DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA PUSKESMAS WAKUMORO KAB MUNA - Kalni, Kalni; Tangalayuk, Agustinus; Mahrani, Sri Wiyati; Ittaqullah, Nurul; Istianandar, Farhan Ramdhani (Jurnal Manajemen dan Kewirausahaan, 2024)
This study aims to determine both simultaneously and partially the effect of work motivation and leadership style on employee performance at the Wakumoro Public Health Center, Muna Regency. The approach of this research is explanatory research. The population of this study were all employees of the Wakumoro Public Health Center, Muna Regency, in Parigi District, Muna Regency, totaling 32 people. This study uses a quantitative approach. Data collection methods in this study were observation, interviews and questionnaires. The results of this study indicate that work motivation and leadership style simultaneously have a positive and significant effect on employee performance, work motivation has a positive and significant effect on employee performance, leadership style has a positive and significant effect on employee performance.